Effect of deposition of nanoparticles during joining of dissimilar metals by friction stir welding - Baridula, Ravinder Reddy (2018)
Friction stir welding (FSW) is a solid–state, hot–shear joining process in which a rotating tool with a pin moves along the butting surfaces of two rigidly clamped plates placed on a backing plate. FSW has evolved as an alternative joining technique for aluminium and is gaining research importance on non-conventional weldable alloys, which improves the strength of the welded joint when compared to the fusion welding process. The earlier research studies on joining of similar and dissimilar metals by varying process parameters to identify change in mechanical properties of weldments can be seen in the literature. In all the studies reported earlier, one can find optimized values of process parameters either for similar or dissimilar alloy joints. Also the composites produced by friction stir processing enhance the mechanical properties of the material. The strength of the welded joint can be further enhanced by the addition of reinforcements into the metal matrix during friction stir welding. Hence, there is a necessity to study the joining of dissimilar aluminium alloys by depositing the nano particles during the friction stir welding. With this motive, the present research aims out to study the effect of dissimilar aluminium alloy joints by depositing nano particles. Experimentation has been carried out on medium strength aluminium alloys AA5052 and AA6063.The effect of copper nanoparticles addition on the strength of welded joint has been studied during friction stir welding. Further, in order to understand the influence of nanoparticles deposition on high strength aluminium alloys AA2024 and AA7075 the reinforcements like multi-walled carbon nanotubes, titanium dioxide and aluminium oxide were studied at various process parameters. The mechanical properties of the welded joint with and without nanoparticles are evaluated which are correlated with the microstructure study by optical microscope. The results show an improvement in mechanical properties due to the addition of nanoparticles in the joints fabricated, compared to that of that of bare joints. The tensile strength and microhardness of the welded joint was improved by 8.01% and 23.7% at 90 mm/min, when compared to the welded joint without CNT nanoparticles for high strength dissimilar aluminium alloys.This behavior was further supported by Electron dispersive X-ray analysis (EDX) study, which provides elemental identification and quantitative compositional information. It has been found that the distribution of nanoparticles was influenced by the groove size and the mechanical properties were found to be enhanced with groove of 1 mm width. It has been observed that the maximum % increase in strength and microhardness for the samples with CNT nanoparticles is about 6.59% and 20%. The improvement of strength and hardness was more with TiO2 nanoparticles.Thus, by controlling the process parameters and groove size the distribution of nanoparticles and mechanical properties of the welded joint were enhanced effectively, but varied depending on the type of reinforcement added during friction stir welding process.